Caracterização anatômica, química e nutricional foliar de Poincianella pyramidalis (Tul.) L. P. Queiroz associada à sua fenofase - Oliveira, Leandro Pereira de (2021)
The Poincianella pyramidalis (Tul.) LP Queiroz is a tree whose foliage is consumed by domestic ruminants in the dry season. local livestock efficiency. Despite the increase in research aimed at sustainable animal production in the Caatinga, the real potential for livestock production is still not known, perhaps due to the lack of knowledge of how native vegetation species behave. Thus, the objective of this work is to characterize the potential use of P. pyramidalis in animal production, from its anato-morphological, histochemical and nutritional characteristics. Leaf samples were collected in different phenophases, comprising young leaves, expanded leaves and senescent leaves (litter) for anatomical, morphological, phytochemical and bromatological analyses. The leaflets of P. pyramidalis present a distinct anatomical pattern and differences in the histolocation of the groups of secondary metabolites according to the stages of development. The anatomical characteristics of the leaves favor rumen degradability, but the presence of secondary metabolites may limit its use. The phytochemical study reveals the presence of groups of secondary metabolites of pharmaceutical interest and chemical characteristics that are relevant in animal production and welfare. The young leaf and the senescent leaf present better chemical-bromatological composition. The senescent leaf stands out for containing the highest carbohydrate content possible to be used by ruminal microorganisms and reflects in greater availability of energy for the animal. P. pyramidalis is an important food source for animals in the semiarid region.